PERBEDAAN KEJADIAN SCABIES BERDASARKAN TINGKAT KEPADATAN HUNIAN TEMPAT TINGGAL DI PONDOK PESANTREN MODERN - Nurmaliza Hasan; Yulnefia Yulnefia; Hidayatul Rahmi (LPPM Universitas Abdurrab, 2025)
Scabies is a contagious skin disease caused by ectoparasites and is a health problem worldwide. Many factors related to scabies cause the prevalence of scabies to continue to increase over time. Residential density is one factor causing the high prevalence of scabies. Different occupancy densities can be found in modern Islamic boarding schools that have dormitories with varying room sizes, one of which is the Modern Islamic Boarding School Diniyyah Pasia Ampek Angkek in Agam Regency, West Sumatra. This study was conducted to determine differences in scabies incidence based on the level of residential density in Islamic boarding schools. This study used an observational analytical method with a cross-sectional approach. The sampling technique was total sampling that had met the inclusion criteria. Data were analyzed using the chi-square test. The results of 219 students showed that 141 (64.4%) students lived in poor residential density, of which approximately 104 (73.8%) students had scabies. Approximately 78 (35.6%) students live with good housing density, of which approximately 36 (46.2%) students have scabies. Based on the chi-square test with P = 0.000, the p value < 0.05 shows a significant difference between the level of housing density and the incidence of scabies. Housing density for residences that meet the requirements of a healthy home and clean living behavior in modern Islamic boarding schools can reduce the incidence of scabies.